Toward robust stability of aircraft electrical power systems: using a μ-based structural singular value to analyze and ensure network stability - Sumsurooah, Sharmila; Odavic, Milijana; Bozhko, Serhiy; Boroyevich, Dushan (Institute of Electrical and Electronics Engineers, 2017)
Transport accounts for nearly two-thirds of the global crude oil consumption and about a quarter of carbon dioxide (CO2) emissions (International Energy Agency 2009, Intergovernmental Panel on Climate Change 2014). The energy use and CO2 emissions in this sector are predicted to increase 80% by 2050 (International Energy Agency 2009). The major contributors of greenhouse effects are expected to be light-duty vehicles (43%), trucks (21%), aviation (20%), and shipping (8%) by 2050 (International Energy Agency 2009). Buses and railways are already sustainable modes of transport. To mitigate the impact of the emissions on climate change, the Intergovernmental Panel on Climate Change, which is the leading international body assessing climate change, recommends a reduction of at least 50% in global CO2 emissions by 2050 (International Energy Agency 2009). This target cannot be met unless there is a deep cut in CO2 emissions from the transportation sector. On the other hand, independent of climate policy actions, the projections are that fossil fuel reserves will become exhausted within the next 50 years. If a more sustainable future is to be achieved, the issues of greenhouse emissions and energy security must be addressed. One long-term solution may well lie in both the adoption of current best technologies and in the development of more advanced technologies, in all sectors of transportation (International Energy Agency 2009). A shift toward more efficient modes of transport, including the more electric aircraft (MEA), are not merely needed, but are required.